2019
DOI: 10.1248/bpb.b19-00199
|View full text |Cite
|
Sign up to set email alerts
|

<i>Spirogyra neglecta</i> Aqueous Extract Attenuates LPS-Induced Renal Inflammation

Abstract: Spirogyra neglecta (SN), commonly named "Tao" in Thai, is a genus of filamentous green macroalgae. SN contains polyphenols such as isoquercetin, catechin, hydroquinone and kaempferol. These constituents exhibit beneficial effects including anti-oxidant, anti-gastric ulcer, anti-hyperglycaemia and anti-hyperlipidaemia in both in vitro and in vivo models. Whether SN extract (SNE) has an anti-inflammatory effect in vivo remains unclear. This study examined the effect of SNE on renal function and renal organic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…According to the extracts from S. neglecta inhibited NO production, indicating the anti-inflammatory activity of S. neglecta. The finding in this study is in line with the study by Ontawong et al [32], who revealed that S neglecta aqueous extract attenuates LPS-Induced renal Inflammation [4], also found that oral administration of S. neglecta alleviated adverse effects of diabetes on inflammatory factors in diabetic rats. Furthermore, Yosboonruang et al [1], reported that S. neglecta possesses anti-inflammatory activity by reducing the release of TNF-α from macrophages.…”
Section: Anti-inflammatory Activitysupporting
confidence: 93%
“…According to the extracts from S. neglecta inhibited NO production, indicating the anti-inflammatory activity of S. neglecta. The finding in this study is in line with the study by Ontawong et al [32], who revealed that S neglecta aqueous extract attenuates LPS-Induced renal Inflammation [4], also found that oral administration of S. neglecta alleviated adverse effects of diabetes on inflammatory factors in diabetic rats. Furthermore, Yosboonruang et al [1], reported that S. neglecta possesses anti-inflammatory activity by reducing the release of TNF-α from macrophages.…”
Section: Anti-inflammatory Activitysupporting
confidence: 93%
“…25 Kaempferol can repair mesangial cells and improve renal injury and fibrosis. 26,27 Studies [28][29][30] have also shown that quercetin can resist inflammation and oxidative stress by inhibiting TNF, IL6, and MAPK14, thereby reducing kidney damage.…”
Section: Discussionmentioning
confidence: 99%
“…Raw264.7 macrophages are commonly used to explore kidney disease related to inflammation in vitro [27,28]. As a main component of the cell wall of gram-negative bacteria, LPS widely used to cause inflammatory response in vitro and in vivo, including kidney disease [29,30]. To validate our hypothesis that hnRNPK binding FLIP in NLRP3 inflammasome activation, we first prepared a peripheral inflammation model with LPS-stimulated Raw264.7 macrophages to investigate whether hnRNPK participates in activation of inflammatory macrophages by regulating cellular inflammation reaction.…”
Section: Introductionmentioning
confidence: 99%